Instytucjonalizacja współpracy w zakresie grobownictwa wojennego - Szymoniczek, Joanna (Rocznik Polsko-Niemiecki, 2015)
Resting places of fallen soldiers – war cemeteries – are monuments to soldiers’ heroism, and thus are of special significance not only for those who have lost their loved ones, but also for entire nations, countries and communities. Therefore, such cemeteries are created under the provisions of relevant authorities, and then put under the special protection of the public. These issues are closely regulated by international law established throughout the twentieth century. Cemeteries are protected by the state on whose territory individual objects are placed. However, the problem of cemeteries is more and more often the responsibility of social organizations. According to the international humanitarian law of armed conflict, specific tasks in this respect are assigned to the tracing services of Red Cross and Red Crescent societies, who deal with the registry of exhumation, inhumation and body transfer, hold deposits, establish the fate of victims of war and issue death certificates. Institutions that deal with exploration, keeping records, exhumation of remains and the construction or revaluation of the graves of fallen citizens buried outside the borders of their own countries include the Council for the Protection of Struggle and Martyrdom Sites, the German People’s Union for the Care of War Graves, the Commonwealth War Graves Commission, the Austrian Red Cross (Österreichisches Schwarzes Kreuz), the American Battle Monuments Commission, the US Commission for the Preservation of America’s Heritage Abroad and the Italian Commissariat General for the Memory of Killed in War (Commissariato Generale per le Onoranze Caduti in Guerra). For political reasons, tasks related to war cemeteries are assigned to social organizations, because their actions are believed to be more effective and less bureaucratic than those of states.